2005
DOI: 10.3748/wjg.v11.i25.3834
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary intake and genetic factors on hypermethylation of thehMLH1gene promoter in gastric cancer

Abstract: Abstract Abstract AbstractAIM: Hypermethylation of the promoter of the hMLH1 gene, which plays an important role in mismatch repair during DNA replication, occurs in more than 30% of human gastric cancer tissues. The purpose of this study was to investigate the effects of environmental factors, genetic polymorphisms of major metabolic enzymes, and microsatellite instability on hypermethylation of the promoter of the hMLH1 gene in gastric cancer. METHODS:Data were obtained from a hospital-based, case-control st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 53 publications
1
38
2
Order By: Relevance
“…Of the four included Asian studies, one showed a significant increase in risk, the other three presented non-significant associations in opposite directions. 39,40,42,45 Diverse results were also found in the two studies involving Caucasians. 43,44 One study on this polymorphism shown in Table 1 was excluded from meta-analysis because the allele frequencies were not reported by the original article.…”
Section: Resultsmentioning
confidence: 71%
“…Of the four included Asian studies, one showed a significant increase in risk, the other three presented non-significant associations in opposite directions. 39,40,42,45 Diverse results were also found in the two studies involving Caucasians. 43,44 One study on this polymorphism shown in Table 1 was excluded from meta-analysis because the allele frequencies were not reported by the original article.…”
Section: Resultsmentioning
confidence: 71%
“…The positive assoc between low fruit or vegetable intake was modified by selected polymorphisms in XRCC1, XPD, MGMT (P interaction = 0.1-0.2) Nan et al [26] ,…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, Nan et al [26] found that high vegetable intake and low potato intake were associated with an increased risk of gastric cancer caused by hypermethylation of the hMLH1 promoter, which is correlated with the loss of gene expression in South Korea. It is assumed that pickled vegetables are a major source of vegetables in Korean diets; thus, high salt consumption may affect gastric carcinogenesis [27] .…”
Section: No Assoc No Assoc No Interactionmentioning
confidence: 99%
“…13 articles were excluded after reading the full text. Six were not Asians studies (Gonzalez et al, 2004;Martinez et al, 2006;Ruzzo et al, 2007;Wideroff et al, 2007;Zendehdel et al, 2009;Garcia-Gonzalez et al, 2012), and seven were repeating or overlapping publications (Cai et al, 1999;Setiawan et al, 2001;Gao et al, 2002b;Qian et al, 2003;Sheng et al, 2004;Nan et al, 2005b;Tripathi et al, 2008). Finally, 39 articles that report on the effects of GSTT1 polymorphisms on gastric cancer in Asia covering in total of 7,737 gastric cancer cases and 10,823 controls were remained for data extraction.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%